Resignation: Expressive Semantic Evolution of a Borrowing and a Precedent Name - A. V. Sharavin; O. E. Voronichev; I. L. Startseva (Научный диалог, 2024)
This article explores the narrowly used borrowing from French, résignation (with Russian graphic variants rezinyatsiya and rezignatsiya), which paradoxically combines features of exoticism, neologism, and archaism in contemporary Russian. The evolution of this lexeme, denoting a particular psychological state, is traced on Russian soil — from its introduction into the Russian in the late 18th century via German transit, spurred by the popularity of Schiller’s eponymous elegy among the progressive Russian intelligentsia, to its attainment of the status of a precedent name and its additional semantic nuances and connotations in the works of I. S. Turgenev and other domestic writers. The article analyzes possible reasons for the decline of this lexeme, which failed to enter active usage and instead receded into passive vocabulary: the lack of a uniform Cyrillic spelling variant, the absence of a productive word formation family, an aura of elitism, and associative links to roots in Russian words such as rezat’ (to cut) and rezkiy (sharp), resulting in a phonetic disadvantage compared to Russian synonyms like pokornost’ (submission) and smireniye (humility).